Methodology for identifying the effective proportion of educational activities for the purpose of conducting distance learning without losing the quality of the educational process - Konstantinov Ilia; Zhuleva Anna; Shavelkin Denis (SHS Web of Conferences, 2022)
The pandemic of the new coronavirus infection has significantly affected all areas of society in all countries of the world, the education sector is no exception. In view of the rapid spread of the growth of morbidity, many universities were forced to abandon the traditional educational model and switch to a remote mode of operation. However, such a transition raises a serious question about the quality of training of students. This paper analyzes the effectiveness of distance learning in one of the technical specialties of the Moscow Aviation Institute (National Research University). This analysis contains various statistical data. This study shows that although distance learning forms have a number of positive aspects, they also have a number of negative factors, in view of which a complete transition from the classical educational model to the distance form is impossible.